Heat transfer to Newtonian and non-Newtonian fluids in cross-corrugated chevron-type plate heat exchangers: numerical approach - Fernandes, Carla S. (2010)
Food fluids are frequently processed in plate heat exchangers (PHEs) and usually behave as non-Newtonian fluids, this behaviour being scarcely considered for PHEs design purposes. Moreover, many food fluids processed in PHEs have a high viscosity and, therefore, data obtained in laminar flow regime is useful to practical applications. The thermal-hydraulic performance of PHEs is strongly dependent on the physical properties of the fluid and on the geometrical properties of the plates namely, on the corrugation angle and on the channel aspect ratio. The mostly widely used PHEs have corrugations of the chevron type with an area enlargement factor defined as the ratio between the effective plate area and projected plate area close to 1.17. In the present work non-isothermal laminar flows of Newtonian and power-law fluids through cross-corrugated chevron-type plate heat exchangers are studied numerically in terms of the geometry of the channels. The plates area enlargement factor was a typical one (1.17), the corrugation angle varied between 30º and 60º and the flow index behaviour, n, between 0.25 and 1. The numerical calculations were performed using the commercial finite element software package POLYFLOW®. The equations solved were the conservation of mass, momentum and energy equations for laminar incompressible flow of Newtonian and power-law fluids. The simulations were performed using channels containing seven consecutive unitary cells, since thermal and hydraulic fully developed flows were achieved in the fifth or sixth consecutive cell, as described in previous works. Coefficient K from the friction curves fRe = K compares very well with experimental and semi-theoretical data for all (seven) values of corrugation angle. Nusselt number reaches a maximum in the interior of the studied corrugation angle range, for a fixed Reynolds, Re, number. Shear thinning effects greatly affect the thermal-hydraulic performance of the plate heat exchangers